Sonic Hedgehog Activation Is Implicated in Diosgenin-Induced Megakaryocytic Differentiation of Human Erythroleukemia Cells - Ghezali, Lamia (Public Library of Science, 2014)
Differentiation therapy is a means to treat cancer and is induced by different agents with low toxicity and more specificity than traditional ones. Diosgenin, a plant steroid, is able to induce megakaryocytic differentiation or apoptosis in human HEL erythroleukemia cells in a dose-dependent manner. However, the exact mechanism by which diosgenin induces megakaryocytic differentiation has not been elucidated. In this study, we studied the involvement of Sonic Hedgehog in megakaryocytic differentiation induced by diosgenin in HEL cells. First, we showed that different elements of the Hedgehog pathway are expressed in our model by qRT-PCR. Then, we focused our interest on key elements in the Sonic Hedgehog pathway: Smoothened receptor, GLI transcription factor and the ligand Sonic Hedgehog. We showed that Smoothened and Sonic Hedgehog were overexpressed in disogenin-treated cells and that GLI transcription factors were activated. Then, we showed that SMO inhibition using siSMO or the GLI antagonist GANT-61, blocked megakaryocytic differentiation induced by diosgenin in HEL cells. Furthermore, we demonstrated that Sonic Hedgehog pathway inhibition led to inhibition of ERK1/2 activation, a major physiological pathway involved in megakaryocytic differentiation. In conclusion, our study reports, for the first time, a crucial role for the Sonic Hedgehog pathway in diosgenin-induced megakaryocytic differentiation in HEL cells.